Bio-preservation of white brined cheese (Feta) by using probiotic bacteria immobilized in bacterial cellulose: Optimization by response surface method and characterization. (January 2020) - Motalebi Moghanjougi, Zahra; Rezazadeh Bari, Mahmoud; Alizadeh Khaledabad, Mohammad; Almasi, Hadi; Amiri, Saber
Abstract: The aim of this research was to prepare bacterial cellulose film (BCF) containing free and microencapsulated Lactobacillus acidophilus and Bifidobacterium animalis with sodium alginate (SA) and pectin. The particle size of microcapsules and the vitality of probiotics were investigated. Moreover, the antifungal effects of the bioactive films and their effect on chemical characteristics of white brined cheese were studied during 45 days of storage. SA stabilized microcapsules had lower particle size and also exhibited higher viability of probiotics in comparison to pectin microencapsulated bacteria. The results showed that the L. acidophilus encapsulated in SA had the highest effect on the inhibitory growth of Aspergillus niger in cheese after 45 days of storage. Chemical properties of cheese including moisture, salt and pH were not affected by the type of bacterium and type of microcapsule. According to the results, the BCF containing microcapsules of L. acidophilus in SA was selected as the best bioactive film. SEM images showed the dispersed and embedded microcapsules in the porous network of cellulose. The XRD results approved the change in the crystalline structure of BCF after incorporation of microcapsules. This study confirmed the potential of bioactive BCF for inhibition of fungal growth in white brined cheese. Highlights: L. acidophilus and B. animalis subsp. lactis were immobilized in BC film (BCF). Encapsulation with pectin and sodium alginate improved the survivability of bacteria. Bioactive BCF membranes showed inhibitory effect on mold growth in Feta cheese. Structure and morphology of BCF samples were determined by FT-IR, XRD and SEM. The probiotic cells immobilized BCF can be suggested as a bio-preservative of cheese.